Peningkatan Literasi Keuangan bagi Pelaku Usaha Mikro di Wilayah Desa Banjarsari - Prasetyo, Hendra Dwi; Komariyah, Fitri; Sadiqin, Amin; Wahib, Moh. (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2025)
Micro-entrepreneurs in Banjarsari Village face constraints in financial management that impact the sustainability of their businesses. This community service program aims to improve financial literacy by providing training and mentoring to micro-entrepreneurs. The methods used include interactive training, financial management simulations, and introduction to relevant digital financial applications. The program results showed an increase in participants' understanding of financial literacy concepts, including cash flow management, daily financial recording, and budget planning. Participants were also better able to utilise technology to support business financial management. The program succeeded in encouraging better financial practices among micro-entrepreneurs, thereby contributing to the increased sustainability and development of their businesses.